Perbedaan Hasil Belajar PKn Siswa Melalui Metode Numbered Head Together (NHT) dan Metode Ceramah di SMAN 1 Pangkalan - SUBHA, LAILATUL; LANIN, DASMAN; FRINALDI, ALDRI (Fakultas Ilmu Sosial Universitas Negeri Padang, 2012)
This study aimed to see differences in learning outcomes of Civics among students of SMAN 1 Pangkalan through the use of Numbered Head Together (NHT) method compared to the use of lecture method in the same subjects. This is a quantitative research using a design approach of quasy experiment. Data were analyzed by using the t test. Based on the experiments and the t-test the result of this study indicated that the mean in the experimental class (NHT class) amounted to 83.80% and the mean of the control class (lecture class) obtained a mean of 76.00%. The t-test results indicated that there are significant differences between the use of NHT and the use of lecture method in the level of 0.05 (5%). In other words NHT method is more effective than the lecture one. Kata Kunci: Hasil belajar, metode NHT, metode ceramah